AKIBAT HUKUM WANPRESTASI DAN TANGGUNG JAWAB PARA PIHAK DALAM TRANSAKSI ANJAK PIUTANG - Sudjana, Sudjana (Faculty of Law, Parahyangan Catholic University, 2019)
In this article, using a juridical-normative approach, the author discusses legal issues stemming from the breach of two interlocking contracts: supplier agreement and factoring agreement. To be analysed is the legal relationship of all parties in the case of breach of contract or worse bankruptcy of the supplier. Issues to be raised in particular concerns who in the case of breach of contract will in the end possess the right to demand payment of outstanding debts and who bear the (legal and financial) risk in the worst case scenario: bankruptcy of buyer.